RISIKO SISTEMATIS MEMEDIASI FAKTOR - FAKTOR FUNDAMENTAL MAKROEKONOMI DAN RETURN SAHAM - Rifa’i, Moh (Students Journal of Economic and Management, 2012)
The purpose of this research is to analysis influence of macroeconomic fundamental factors are exchange rate, interest rate, inflation, and economic growth toward stock return with systematic risk by intervening variabel. This research use secondary data from indonesian Capital Market Directory (ICMD) publication and data from BPS. The sample of this study are manufacture firm in food & beverage sector listed in indonesian Stock Exchange in 2006-2010. The sampling technical used purposive sampling and total sampel is 15 firms with 75 observation sample. The analysis with multiple linier regression. The result of this research showed the all macroeconomic variable are not influence toward systematic risk. And only exchange rate and inflation variable are significant influence toward stock return. while the systematic risk is not influence toward stock return. The systematic risk variabel is not intervening variable between macroeconomic variable and stock return. The R-square is 0,519 showed the five independent variable can predict stock return. Key words: exchange rate, interest rate, inflation, economic growth, systematic risk and stock return.